Experimental Studies on Grain Material Extruding Process. (2017) - Kushnir, V.; Gavrilov, N.; Kim, S.
Abstract: The article presents the results of studies on the processing of crops materials. The method of experimental studies was described. The way of effective preparation was determined - it was the preparation of fodder mixes, combined feed. Grain mixes were taken as a basis of the constituting fodder mix. Investigations were carried out on an extruder PE-20 in Kostanay State University named after A. Baitursynov and based on enterprise LLP "Agro Tech Service-12". The technical characteristics of the extruder were given; (basic instruments and equipment for experiments; standards, and standards of the determine quality of the extrudate). The technique of conducting investigational studies was developed. The device of an extruder and the features design die were described. The mass of the sample was found in one second extruding, and then the hourly productivity was calculated. The methods of processing of results of strain-gage testing axial force were shown. The results in the form of graphs showing the change in the performance and capacity of the extruder are presented on the basis of research.